2016
DOI: 10.5897/ajpp2015.4406
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of oxytocin in pregnancy, parturition and postpartum for Nigerian females in Zaria, Nigeria

Abstract: Oxytocin is a hormone involved with adjustment of pregnancy, the process of delivery, breastfeeding, social recognition and bonding. This study aimed at determining the serum levels of oxytocin in pregnancy, during labour, and in the puerperium for Nigerian females in Zaria. It was a cross-sectional study of one hundred and twenty women aged 18 to 45 years from four hospitals in Zaria. The women were grouped into four groups comprising non-pregnant women (control), pregnant women (first, second, and third trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…For the following experiment, we treated pregnant rats with atosiban from GD 10 to GD 17 to block the endogenous OXT signaling. It has been known that the endogenous OXT levels are increased following gestational age in animal and human [24,39,40]. The results showed that plasma E2 levels and its synthesizing enzyme, CYP19A1, were decreased in atosiban-treated animals.…”
Section: Discussionmentioning
confidence: 94%
“…For the following experiment, we treated pregnant rats with atosiban from GD 10 to GD 17 to block the endogenous OXT signaling. It has been known that the endogenous OXT levels are increased following gestational age in animal and human [24,39,40]. The results showed that plasma E2 levels and its synthesizing enzyme, CYP19A1, were decreased in atosiban-treated animals.…”
Section: Discussionmentioning
confidence: 94%
“…The concentration was determined as per the manufacturer’s protocol and by measuring the end-point colour intensity using a spectrophotometer at 450 nm. 26 …”
Section: Methodsmentioning
confidence: 99%
“…The concentration was determined as per the manufacturer's protocol and by measuring the end-point colour intensity using a spectrophotometer at 450 nm. 26 Cortisol and prolactin (PRL): the maternal cortisol and prolactin in serum were determined by competitive ELISA kits, DiaMetra ELISA 28 and EIA kit respectively. 29…”
Section: Quantification Of Serum Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…6 There are some studies stating that the range of oxytocin is less in non-pregnant women, it may increase during pregnancy. 7 Papaya is also called pawpaw, kates, and papaw. The botanical name is Carica papaya, belonging to the Caricaceae family.…”
Section: Introductionmentioning
confidence: 99%